How to overcome the governance challenges of implementing NREGA: Insights from Bihar using process-influence mapping - Raabe, Katharina; Birner, Regina; Sekher, Madhushree; Gayathridevi, K. G.; Shilpi, Amrita; Schiffer, Eva (International Food Policy Research Institute, 2010)
Large-scale social safety net programs such as India's National Rural Employment Guarantee Act (NREGA) are difficult to implement due to governance challenges related to elite capture, leakages, and corruption. The ability to identify how the governance challenges of program implementation can be met requires detailed insights into the actual process of program implementation, with clear views on the source of leakage and mismanagement, the sensitivity of program implementation to the influence of different actors, local power structures and informal bureaucratic processes. This paper uses a new participatory research method, referred to as Process-Influence Mapping, to shed light on these issues and related governance challenges, using the implementation of NREGA as an example. The Process-Influence Mapping tool helps identify the specific features of the NREGA implementation process that limit the program's effectiveness (for example, elite capture in the definition of work and capacity limitations due to staff shortages and lack of training) and create scope for the misappropriation of funds. The insights gained can be used to identify policy options for reforming the administrative process of NREGA implementation so as to create an effective social safety net.